Polypropylene microplastic exposure modulates multiple metabolic pathways in tobacco leaves, impacting lignin biosynthesis - Muhammad Arshad; Yaowu Ma; Weichang Gao; Shixiang Zhang; Muhammad Shoaib; Xinru Liu; Yingkai Fan; Gen Li; Huiyu Chuai; Ying Jiang; Jiaguo Jiao; Huijuan Zhang; et al. (Ecotoxicology and Environmental Safety)
The adverse effects of microplastics (MPs) and nanoplastics (NPs) on plant growth have gained significant attention. However, the response of tobacco plants to polypropylene microplastics (PP-MPs) remains poorly understood. To address this, a microcosm experiment was conducted in which tobacco seedlings were exposed to PP-MPs at varying concentrations (100 and 1000 mg/kg) and particle sizes (20 nm and 100 µm) for 48 days in red soil. The physicochemical, transcriptomic, and metabolic responses of tobacco plants to PP-MP treatments were assessed. Our findings indicate that the effect of PP-MP exposure on tobacco growth was dose-dependent, with the higher doses (1000 mg/kg) inducing significantly stronger responses. Further, a significant accumulation of key metabolites in the phenylpropanoid and flavonoid biosynthesis pathways such as quercetin, phloretin, kaempferol, liquiritigenin, naringin, myricetin, ferulic acid, formaldehyde, and methyl eugenol was observed in response to PP-MPs. Additionally, the transcriptomic analysis revealed that higher doses enriched more DEGs than lower. KEGG pathway analysis identified significant enrichment in phenylpropanoid biosynthesis, flavonoid biosynthesis, sesquiterpenoid and triterpenoid biosynthesis, and plant hormone signal transduction. The notable variation in the expression of key enzyme-related genes such as PAL, CHI, CSE, C4H, 4CL, COMT, and CYP indicates the substantial impact on lignin synthesis. Lastly, large-sized PPMPs alter the activity of key lignin-degrading enzymes, affecting the lignin content. This study offers valuable insights into the responses of tobacco plants to varying concentrations and sizes of PP-MPs, integrating both physicochemical and molecular perspectives.